Serum copper, zinc an selenium levels in women with unexplained infertility in Ibadan Nigeria: a cross-sectional analytical study (2023)
Background: Infertility is a global public health issue affecting couples. Trace metals have been implicated in effective reproductive functions in males but less studied in females. Objective: To compare the serum levels of copper (Cu), zinc (Zn), selenium (Se) and copper/zinc ratio in women with unexplained infertility and fertile women. Subjects and Methods: This was a cross-sectional analytical study that compared 75 consenting women who had unexplained infertility with 74 fertile women that were controls. Both groups were seen within 1 year of delivery and were recruited from the family planning unit, at the University College Hospital, Ibadan. Data were obtained through a semi-structured questionnaire, after which 10 mL of venous blood was collected. Analysis of selected trace elements were done by atomic absorption spectrophotometry. IBM SPSS version 23 was utilized for data analysis and the levels of statistical significance was set at <0.05. Results: The mean (±SD) serum concentrations of Cu (93.11 ± 16.55 μg/dL), Zn (72.04 ± 15.03 μg/dL) and Se (28.28±8.33 μg/dL) amongst the women with unexplained infertility were lower when compared to the control group (all with P<0.001). The serum Cu/Zn ratio was higher among the fertile women, though not statistically significant (P<0.62). Age of <35 years was associated with normal serum levels of Cu (P<0.01), while women with normal body mass index had low serum concentrations of Cu (P=0.04), amongst the fertile group. Conclusion: Serum copper, zinc and selenium concentrations are significantly lower in women with unexplained infertility, therefore diets or supplements containing these trace elements may be helpful in their management.